2019
DOI: 10.3906/sag-1810-65
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for rectal colonization of carbapenem-resistant Enterobacteriaceae in a tertiary care hospital: a case-control study from Turkey

Abstract: Background/aim This study aimed to evaluate the risk factors of patients colonized with carbapenem-resistant Enterobacteriaceae (CRE). Materials and methods The study was conducted between January 2010 and March 2016. The colonized group consisted of patients who had a CRE strain in their rectal swab cultures, whereas patients with negative rectal surveillance cultures for CRE who were concurrently hospitalized in the same units with the colonized group patients were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
2
2
0
1
Order By: Relevance
“…On univariate analysis, as in previous studies, [9][10][11]17,[21][22][23] we found that risk factors for both CP-CRE colonization and non-CP-CRE colonization included nursing home residency before hospital admission, antibiotic treatment 3 months before admission, urinary catheter, decubitus ulcer, and mechanical ventilation. We did not find men to be at an increased risk for CP-CRE or non-CP-CRE colonization in comparison to other studies, 9,10 which may have been due to an older patient population in our study and the longer life expectancy of women in Israel.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…On univariate analysis, as in previous studies, [9][10][11]17,[21][22][23] we found that risk factors for both CP-CRE colonization and non-CP-CRE colonization included nursing home residency before hospital admission, antibiotic treatment 3 months before admission, urinary catheter, decubitus ulcer, and mechanical ventilation. We did not find men to be at an increased risk for CP-CRE or non-CP-CRE colonization in comparison to other studies, 9,10 which may have been due to an older patient population in our study and the longer life expectancy of women in Israel.…”
Section: Discussionsupporting
confidence: 78%
“…On multivariate analysis, as in previous studies, 11,23 we demonstrated that predictors for CP-CRE colonization and for non-CP-CRE colonization included nursing home residency before hospital admission, antibiotic treatment 3 months before admission, and having a decubitus ulcer. In our study, risk factors unique for non-CP-CRE colonization (and not for CP-CRE colonization) included mechanical ventilation and patient movement between various hospital departments.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Like Klebsiella, Raoultella can acquire antibiotic resistance genes, leading to an increase of the multidrug‐resistant (MDR) isolates. Recent work describing infections caused by Raoultella has shown that these bacteria are characterized by various resistance mechanisms, especially those involving sulfonamides and quinolone and antibiotics of the β ‐lactam spectrum 12,13 . Resistance genes for such drugs are localized in bacterial plasmids; they are not a constitutive component of their genome.…”
Section: Discussionmentioning
confidence: 99%
“…Karbapeneme dirençli Enterobacteriaceae ailesi üyelerinin neden olduğu enfeksiyonlar Türkiye' de ve tüm dünyada önemli bir sorundur (1)(2)(3)(4). Karbapenem direnci;…”
Section: Introductionunclassified